Development of a clinical learning model to enhance patient safety awareness competency among Thai nursing students - Jutarat Bandansin; Danulada Jamjuree; Manat Boonprakob; Saisamorn Chaleoykitti (Belitung Nursing Journal, 2022)
Background: Enhancing patient safety awareness competency in nursing students is a necessity as they will be the next generation of professional nurses to take care of patients. One of the strategies is to create an innovative learning model using questioning as part of the metacognitive thinking concept. Objective: This study aimed to develop a clinical learning model to enhance patient safety awareness competency among Thai nursing students and determine its effectiveness. Methods: The study used a research and development design with two phases: (1) the development of a clinical learning model to enhance patient safety awareness competency among nursing students, and (2) the evaluation of the effectiveness of the developed clinical learning model. The evaluation was done quantitatively and qualitatively. In the quantitative strand, a quasi-experimental method using repeated measures design was used in 24 students. While in the qualitative strand, a qualitative descriptive design was employed in 24 students and three teachers. Results: In the first phase, the DUIR clinical learning model was developed, consisting of four processes: 1) Doubt (D), 2) Understanding (U), 3) Insight (I), and 4) Reflected value (R). The patient safety awareness competency included two components: managing patient safety and solving problems related to unsafe patient care. In the second phase, the model was evaluated by the students and the teachers. It revealed that nursing students’ patient safety awareness competency was very high, and the competency was statistically different before and after the learning model. Conclusion: The developed DUIR learning model using a questioning strategy is considered effective to encourage students to reflect critically on their own clinical experiences in order to achieve quality and safe care outcomes, thereby enhancing patient safety awareness for nursing students in a sustainable way. This model serves as an input for Thai nursing education and beyond.